Perforated appendicitis induced by pembrolizumab: a case report and review of the literature. Issue 2 (17th September 2021) - Papageorgiou, Georgios I.; Fergadis, Evangelos; Skouteris, Nikos; Christakos, Evridiki; Tsakatikas, Sergios A.; Filippakou, Aikaterini; Papantoni, Evangelia; Stanc, Gabriela; Souka, Efthymia; Valavanis, Christos; Kosmas, Christos
Abstract : Monoclonal antibodies against programmed cell death protein 1 (PD-1) and PD-1 ligand 1 (PD-L1) are the main representatives in the field of immunotherapy and their indications are constantly increasing in medical oncology and hematology during the last decade. They are associated with long-lasting responses and an acceptable toxicity profile, although they may infrequently cause life-threatening complications requiring prolonged hospitalization or urgent interventions. With the current report, we present the case of a 75-year-old woman diagnosed with stage IV lung adenocarcinoma, who developed acute abdominal pain without preceding symptomatology while on pembrolizumab-pemetrexed maintenance treatment. A contained rupture of the appendix was found, for which she was managed conservatively. Subsequent endoscopic as well as histopathological findings from biopsies obtained via colonoscopy associated the clinical and imaging findings with grade 4 immune-mediated colitis. Interestingly, high-grade colitis is more frequent with anti-CTLA-4 agents in comparison to anti-PD-1 agents; moreover, most cases of anti-PD-1-mediated colitis present with preceding symptomatology (like diarrhea or vomiting), while cases or colonic perforation are extremely rare if ever described.